Master’s Degree Programme in Russia: a Conscious Choice for International Students? - E. M. Rogova; D. V. Kochetkova (Открытое образование (Москва))
In recent decades, there has been a significant increase in the number of students worldwide choosing to study abroad. In 2014, according to the Organization for Economic Cooperation and Development, about five million students studied abroad. The development of distance learning technologies contributes to the growth of mobility.Russia is an attractive destination for students’ mobility, both shortterm and long-term, and Russian universities compete for students in global markets. The internationalization of education, the increase in the number of international students at degree programs set new requirements for host universities, which should be taken into account in their strategies. This is the presence of a developed infrastructure at the university (laboratory equipment, well-equipped classrooms, modern dormitories, a library with access to a large number of electronic resources, etc.), high quality of teaching, accessible and friendly living environment at the university. In addition, various external factors that characterize the accessibility and attractiveness of the city and the country are important.The goal of our research is to identify the factors that are important for foreign students to choose Russian universities for master’s studies. The master’s level assumes that students themselves make an informed decision about studying abroad, as well as about the choice of country and direction of study, and also better understand what advantages foreign learning experience gives.The study was conducted by interviewing foreign students enrolled in Master’s programs at the National Research University Higher School of Economics in St. Petersburg. The choice of this particular educational institution is due to the high proportion of foreign students enrolled in Master’s programs (on English-language programs their share reaches 40%, and on average is about 13%); the presence of several programs of prestigious international accreditations, network programs (double diplomas, consortiums) and, in general, high positions of the university in international rankings; as well as the wide range of master programs for different areas of study. The survey involved foreign students enrolled in master’s programs (excluding short-term mobility programs). As a result, it was revealed that the reputation of the university, the availability of scholarship programs and grants, employment prospects in Russia or abroad after graduation, simplicity and transparency of the enrollment procedure are crucial for master’s students intending to study in Russia.The results obtained on the basis of a survey of students make it possible to clarify the set of factors identified from the analysis of the literature that affect students’ decision-making about their training in the Master’s programs in Russia. Their practical significance lies in the fact that they can be taken into account when developing university strategies and programs, as well as marketing campaigns aimed at attracting foreign graduate students.